SIMPLIFIED TECHNICAL ENGLISH IN MIRCE MECHANICS - Knežević, Jezdimir; Chiarello, Orlando (Journal of Applied Engineering Science, 2013)
The second Axiom of Mirce Mechanics, states, “The probability of faulty execution of any maintenance task is greater than zero”. Analysis of maintenance processes clearly shows that ineffective communication between system designers and maintenance personnel, through maintenance documentation, is a well-recognised contributor to the occurrence of faulty maintenance task, which in turn could have a significant impact on reliability, availability, safety, cost and effectiveness of technical systems. This paper addresses the lack of understanding of maintenance manuals, written in English, by 80% of the global maintenance personnel whose native language is not English. The majority of them have knowledge of English that is rather limited and are easily confused by complex sentence structures and by the number of meanings and synonyms that English words may have. Significant improvements in the direction of effective communication have been achieved by the creation and use of Simplified Technical English, the benefit of which is presented in this paper.